Desenvolvimento e validação de um método automatizado para a quantificação dos níveis séricos de nitrito/nitrato - Tatsch, Etiane (2012)
Nitric oxide (NO) is a reactive free radical, acting as a messenger molecule, mediating several functions, including vasodilation, platelet aggregation inhibition and neurotransmission. Because this radical to have a short half-life, its determination is difficult, therefore, measurement of metabolites nitrite/nitrate (NOx) is most often used to evaluate NO production. The Griess reaction is the most used method for NOx quantification due to its simplicity, speed and cost-effective. Due to the biological relevance of NO, it is extremely importance to its measurement. The objective of this study was to develop and validate an analytical method for the automated measurement of serum levels of NOx by the Griess method using the Cobas Mira clinical chemistry analyzer. This study provided the development of a protocol for the automated measurement of serum levels of NOx, which is linear method (r2= 0.993, P <0.001), precise, because it showed a coefficient of variation in intra-assay precision of 8.7% and inter-assay precision of 5.6%. Moreover, we observed a recovery of 114.6% which is considered accurate study. Thus, it was concluded that the automated method presented here is linear, precise, accurate, simple and low cost, likely to be adapted to Cobas Mira analyzer and other automated systems available in clinical routine laboratory.